Assessment of the quality of oral squamous cell carcinoma clinical records in oral surgery with Surgical Tool for Auditing Records (STAR) scoring - Pravallika Kakada; Karthikeyan Ramalingam; Pratibha Ramani; Murugesan Krishnan (BMC, 2024)
Abstract Background The Surgical Tool for Auditing Records scoring system [STAR] focuses on surgical record auditing with promising outcomes. It offers a structured approach to evaluating the quality of surgical notes. Aims and objectives This study aimed to assess the effectiveness of the STAR in evaluating oral surgical records and identifying areas for improvement in documentation practices. Materials and methods The data was obtained from the Dental Information Archival Software (DIAS) of our institution. The sample size was determined using G*Power 3.1.9.4 software. Fifty consecutive oral surgery clinical records of oral squamous cell carcinoma patients were evaluated using STAR. Each record was reviewed for adherence to documentation standards including Initial Assessment (10 points), Follow-up Entries (8 points), Consent Documentation (7 points), Anesthesia Report (7 points), Surgical Log (9 points), and Discharge Synopsis (9 points). compiling a total STAR score (50 points). The data was tabulated in Google Sheets. The descriptive statistics with inter-observer agreement and the mean score were recorded. Results We observed that each of the 50 records received a score of 49/50 points on the STAR. Deductions were necessary in the Operative record section due to the lack of information regarding the sutures used. Conclusion To summarize, this study emphasizes the effectiveness of the STAR scoring system in evaluating the quality of oral surgical records. Identifying deficiencies, particularly in documenting operative details, can improve the completeness and accuracy of patient records. It can ultimately enhance patient care and facilitate better communication among healthcare professionals.